From Schools to Family Health Centers: 13-Year-Old Td Vaccination Coverage and Barriers - Feyyaz Barlas; Ufuk Acar (Sağlık Bilimleri Dergisi, 2026)
With the regulation that entered into force on 3 June 2020 in Türkiye, the age 13 diphtheria-tetanus booster dose vaccines, which were administered collectively in schools with mobile service units, were transferred to family health units based on individual application. This study was planned to investigate the Tetanus-Diphtheria vaccination coverage and reasons for non-vaccination among adolescents in Şanlıurfa provincial center after this policy change. This study is a cross-sectional and case-control study conducted in Şanlıurfa Haliliye district in October 2023. The population comprised individuals aged 13 years who were eligible for Tetanus-Diphtheria vaccination; sample size was calculated based on available literature. Face-to-face questionnaires were administered. Participants who remained unvaccinated were placed in the case group, while those vaccinated were assigned to the control group. The Tetanus-Diphtheria vaccination coverage was 77.8%, falling below the World Health Organization’s ≥90% target. The most common reasons for not receiving the vaccine were “lack of awareness about the need for vaccination” (51.3%) and “lack of time/forgetfulness” (27.7%). Completing other childhood vaccinations, receiving a COVID-19 vaccine, and obtaining information from a healthcare provider were associated with higher vaccination rates, whereas citing the media as the main information source, agreeing with anti-vaccine news, a history of previous vaccine hesitancy/refusal, and access barriers were linked to non-vaccination. These findings indicate that insufficient information, accessibility challenges, and mistrust must be addressed simultaneously. A hybrid service model using both school-supported mobile teams and family health centers could increase Tetanus-Diphtheria coverage and improve overall vaccination rates.